La pedagogia di Franco Frabboni - Massimo Baldacci (Firenze University Press, 2011)
This paper takes up and rearrang the lines of interpretation of the work of Frabboni The problematicism (2003). In this essay, the author limits himself to the side of education, but the theory of teaching as a science, which finds complete expression in many other works of Frabboni, will constitute an important cultural contribution by the intellectual of Bologna. it is the comparison of problematicism with the problems of educational practice that derive instances of his rethinking and comparison with this comes the idea of integrated training system(which comes from the idea of "deschooling"). The pedagogy of Frabboni is critical and it is intent on addressing the educational problems in the optics of a problematicism which takes account of the historical times.